Ice chart of the Arctic Ocean between Greenland and Spitzbergen / from observations by Captn. David Gray - Sharbau, H. (Henry); Weller, Edward, 1819-1884 ([London] : [Royal Geographical Society], 1881)
Relief shown by hachures. "Pubd. for the Proceedings of the Royal Geographical Society, 1881." Color; 1:12,000,000